Kinetika Reduksi Isotermal CuO/ZnO dalam Penyiapan Katalis untuk Sintesis Metanol - Hendriyana Hendriyana (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Catalyst Cu/ZnO for methanol synthesis was prepared using coprecipitation method, then followed with calcination at 350oC for 1 hour to obtain CuO/ZnO with a molar ratio of 50:50. Afterward, two gram of CuO/ZnO was treated for reduction to to Cu/ZnO with H2 with a flowrate of 120 mL.min-1 in a semi batch isothermal reactor. This reduction was carried out at temperatures of 170, 200, and 220oC. Since the highest rate of reduction were found at CuO conversions in the range of 30-40%, the kinetic of reduction of CuO/ZnO was represented using modified Prout-Tompkins model ( )n ( )m da / dt = k a +0,3 1-a . This model fit very well to our experimental data with activation energy in of about 25 kJ/mol, frequency factor of about 10 min-1, and m of about 1,1 and n of about 1,4.